Effect of using inoculant on elephant grass silage with additives (Acta Scientiarum. Animal Sciences, 2020)
This study aimed to evaluate the use of inoculant on silage of elephant grass, wet brewery waste and buriti meal at different silo opening times. The experimental silage tested was composed of 50% elephant grass, 30% wet brewery waste, and 20% buriti meal. The experimental design was randomized block in a factorial arrangement (2 x 4), where the treatments consisted of the use or not of inoculant during silage processing, and four silo opening times (7, 14, 21, and 28 days). Data collected were firstly subjected to ANOVA and subsequent Tukey’s test. Results were considered significant at p â‰¤ 0.05. The use of inoculant in silage production provided more acidic pH (p < 0.05) and higher (p < 0.05) effluent losses. Longer silo opening times resulted in more alkaline pH (p < 0.05) and higher (p < 0.05) effluent losses. The use of inoculant in silage production and longer silo opening times provided higher (p < 0.05) content of ash, crude protein, and fats, and lower (p < 0.05) content of dry matter and fiber (neutral and acid detergent). However, there was no interaction between the factors evaluated in this study. It was concluded that the inoculant may be used in the production of elephant grass silages, wet brewery waste, and buriti meal, providing a more acidic pH, higher effluent losses, lower contents of dry matter and fiber, and higher nutritional content. As the opening time was extended up to 28 days, there was more alkaline pH, higher effluent losses, lower dry matter and fiber content, and higher nutritional content.